Pendekatan Arsitektur Hijau Berbasis Healing pada Bangunan Rumah Sakit Khusus Kanker di Palu - Jefriyanto, Jefriyanto; Rahayu, Irma; Herniwati, Andi (The Department of Architecture, Faculty of Science and Technology, Universitas Islam negeri Alauddin Makassar, 2026)
Cancer is one of the diseases with a high mortality rate and requires specialized healthcare services that can support the processes of examination, treatment, care, and patient recovery comprehensively. Palu City, in Central Sulawesi Province, needs a specialized cancer hospital that not only provides medical care but also offers a comfortable, healthy, and healing-supportive environment. This study aims to design a Specialized Cancer Hospital in Palu using a healing-based, green architecture approach to create a healthcare facility that is environmentally friendly, energy-efficient, and patient-centered. The method used is a descriptive, qualitative approach with an architectural design focus, carried out through site observation, literature and precedent studies, interviews, and analysis of spatial needs, site conditions, building form, and the application of design concepts. The design results show that the healing-based green architecture approach is applied through the use of green open spaces, vegetation as shading and noise reduction elements, natural lighting, natural ventilation, rainwater management, environmentally friendly materials, and the provision of a healing garden. This design is expected to create a specialized cancer hospital that is functional, comfortable, sustainable, and supportive of patients' physical and psychological recovery.